2023
DOI: 10.1145/3514233
|View full text |Cite
|
Sign up to set email alerts
|

The Weights Can Be Harmful: Pareto Search versus Weighted Search in Multi-objective Search-based Software Engineering

Abstract: In presence of multiple objectives to be optimized in Search-Based Software Engineering (SBSE), Pareto search has been commonly adopted. It searches for a good approximation of the problem’s Pareto optimal solutions, from which the stakeholders choose the most preferred solution according to their preferences. However, when clear preferences of the stakeholders (e.g., a set of weights which reflect relative importance between objectives) are available prior to the search, weighted search is believed to be the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 108 publications
1
6
0
Order By: Relevance
“…3: d). These result are in line with those by Chen and Li [95], who showed that Pareto search is preferred over weighted search for problems in the Search-Based Software Engineering domain.…”
Section: Rq3: Multi-objective Optimisationsupporting
confidence: 92%
“…3: d). These result are in line with those by Chen and Li [95], who showed that Pareto search is preferred over weighted search for problems in the Search-Based Software Engineering domain.…”
Section: Rq3: Multi-objective Optimisationsupporting
confidence: 92%
“…For the sake of practical illustration, though, the solutions with nearly equal regression residuals for both storage and loss moduli we obtained are numerically close to that reported in the referenced literature. In particular, we were able to approximately reproduce the results obtained by the mentioned monobjective EA [17] for the LDPE material with respect to both regression errors and number of model parameters (indeed, the literature [31] suggests that multiobjective optimization methods can outperform monobjective analogs in virtue of the lower scale sensitivity and susceptibility to local-optima traps-although subject to the limitations of the intrinsic experimental errors in the data sample). Like in the said experiment, the solutions produced by MOAD/D have similar or lower regression residuals than those yielded by deterministic methods reported in the literature (Section 1.2), and with a lower number of parameters.…”
Section: Discussionmentioning
confidence: 53%
“…When information about preferences is lacking, building a significant preference model can be difficult, and it could take many executions with different preference settings in order to find a compliant solution. Furthermore, even when preferences are clear and certain, recent studies show that a priori approaches based on weights can be harmful to the search (Chen and Li, 2022).…”
Section: Problem Definitionmentioning
confidence: 99%